Finite Element Method for Time-Fractional Navier–Stokes Equations with Nonlinear Damping - Shahid Hussain; Xinlong Feng; Arafat Hussain; Ahmed Bakhet (Fractal and Fractional)
We propose a hybrid numerical framework for solving time-fractional Navier–Stokes equations with nonlinear damping. The method combines the finite difference L1 scheme for time discretization of the Caputo derivative (<semantics>0<α<1</semantics>) with mixed finite element methods (P1b–P1 and <semantics>P2</semantics>–<semantics>P1</semantics>) for spatial discretization of velocity and pressure. This approach addresses the key challenges of fractional models, including nonlocality and memory effects, while maintaining stability in the presence of the nonlinear damping term <semantics>γ|u|r−2u</semantics>, for <semantics>r≥2</semantics>. We prove unconditional stability for both semi-discrete and fully discrete schemes and derive optimal error estimates for the velocity and pressure components. Numerical experiments validate the theoretical results. Convergence tests using exact solutions, along with benchmark problems such as backward-facing channel flow and lid-driven cavity flow, confirm the accuracy and reliability of the method. The computed velocity contours and streamlines show close agreement with analytical expectations. This scheme is particularly effective for capturing anomalous diffusion in Newtonian and turbulent flows, and it offers a strong foundation for future extensions to viscoelastic and biological fluid models.